2017
DOI: 10.1007/s10862-017-9603-0
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Obsessive-Compulsive Beliefs about Controlling One’s Thoughts

Abstract: Cognitive models of obsessive-compulsive disorder propose that beliefs about the importance of and need to control thoughts (ICT) are central to the maintenance of the disorder. Cognitive Bias Modification for Interpretation (CBM-I) can be used to experimentally test this theory and may also have clinical utility as an adjunct therapeutic tool. The current study extended previous research to investigate whether two CBM-I sessions (one within and one outside the laboratory) would augment effects on obsessive-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Before this, we must address the issue that our positive training, relative to neutral training, did not lead to a greater reduction in self-reported symptoms of contaminationrelated OCD. This finding that an increase in adaptive interpretative bias without a subsequent reduction in self-reported OCD symptoms is consistent with a significant proportion of the literature on CBM-I for OCD (Beadel et al, 2014;Black & Grisham, 2018;Stech & Grisham, 2017;Wong et al, 2021b). A possible explanation is that one short training session might have been sufficient to reduce interpretive bias but was an inadequate dose for affecting meaningful change on questionnaires related to the individuals' primary concern, which typically frame symptoms as stable and traitlike constructs (e.g., 'I find it difficult to touch garbage or dirty things').…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Before this, we must address the issue that our positive training, relative to neutral training, did not lead to a greater reduction in self-reported symptoms of contaminationrelated OCD. This finding that an increase in adaptive interpretative bias without a subsequent reduction in self-reported OCD symptoms is consistent with a significant proportion of the literature on CBM-I for OCD (Beadel et al, 2014;Black & Grisham, 2018;Stech & Grisham, 2017;Wong et al, 2021b). A possible explanation is that one short training session might have been sufficient to reduce interpretive bias but was an inadequate dose for affecting meaningful change on questionnaires related to the individuals' primary concern, which typically frame symptoms as stable and traitlike constructs (e.g., 'I find it difficult to touch garbage or dirty things').…”
Section: Discussionsupporting
confidence: 85%
“…CBM-I has seen increasing application in experimental investigations of the proposed causal relation between misappraisals of significance and OCD symptoms. Relative to control training, which differs by study, CBM-I is able to reduce responsibility beliefs (Grisham et al, 2014), beliefs about the importance of and need to control thoughts (Clerkin et al, 2014;Stech & Grisham, 2017), negative beliefs about memory and uncertainty (Black & Grisham, 2018), and perfectionism (Wong et al, 2021b). Unfortunately, CBM-I's clinical application in OCD is currently limited partly because these studies have reported mixed findings regarding its impact on symptom reduction and behaviour.…”
mentioning
confidence: 99%